PENYULUHAN KESEHATAN PERILAKU HIDUP BERSIH DAN SEHAT SELAMA MASA PANDEMI COVID 19 DI PUSKESMAS MUTIARA KABUPATEN PIDIE - Chairanisa Anwar; Syarifah Farany (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2021)
Abstract  Community service activities conducting health education about clean and healthy living behavior in the community have shown that they are significantly effective in increasing public knowledge and attitudes towards the implementation of the rules that have been issued by the government to implement physical and social distancing. Health promotion is the essence of the role of health workers who actually have a positive impact in an effort to increase community participation in improving the health status of toddlers in particular, society and the nation in general. The involvement of religious leaders in the community bridges public acceptance of health programs.Getting used to a clean and healthy lifestyle needs to be applied from now on, especially during this Covid-19 outbreak. PHBS habituation intends to provide a routine activity for someone related to a clean and healthy lifestyle so that it becomes a habit (Wiranata, 2020). The role of parents is very important and influential in the habituation of a clean and healthy lifestyle in the family. Parents are obliged to determine the choice of quality health services for family members such as consuming various types of nutritious food, emotional support, activities of daily living (physical activity), and environmental quality (Inderan and Weta, 2018). Therefore, habituation of a clean and healthy lifestyle for family members in particular and the community during the Covid-19 outbreak can be in the form of education, both theory-based and direct practice. If people get used to a clean and healthy lifestyle from an early age, then indirectly the community has played an active role in fighting COVID-19 in Indonesia.   Keywords: clean and healthy lifestyle